Techno-economic Analysis on the Production of Zinc Sulfide Nanoparticles by Precipitation Assisted Ultrasonic Radiation Method - L Astuti; R P Dewi; A Nurdiana; R Ragadhita; A B D Nandiyanto (Universitas Komputer Indonesia, 2021)
Zinc sulfide is a material that has many uses in various fields. Zinc sulfide is deriving from the mineral sphalerite. The purpose of this study was to evaluate the feasibility of producing zinc sulfide from zinc acetate and sodium sulfide using the precipitation-assisted ultrasonic radiation method. This method is the most efficient method for the synthesis of zinc sulfide nanoparticles, because it does not take much time and the resulting product is high. The evaluation was done from the engineering and economic perspectives. The feasibility analysis method from the engineering perspective was done by designing the initial production design on a large scale, whereas the analysis from an economic perspective was done by calculating various economic parameters, that is Gross Profit Margin, Cumulative Net Present Value, Internal Rate Return, Payback Period, Break Event Point, and Profitability Index. The engineering perspective showed that the production of zinc sulfide nanoparticles can be done on a large scale due to the commercial availability of materials and tools. Based on the economic evaluation, the production of zinc sulfide nanoparticles by precipitation-assisted ultrasonic method is ideal for an industrial scale. Earned increased profits over 20 years, the payback on investment costs lasted only two years. We hope that this study can provide references to readers, industry, and researchers regarding the feasibility analysis of the production of zinc sulfide nanoparticles using the precipitation-assisted ultrasonic radiation method.